Оцінювання діяльності державних службовців: європейський досвід правового регулювання - Кірмач, А.В. (Часопис Київського університету права, 2009)
В научной статье автор анализирует теоретические и практические аспекты оценивания деятельности и аттестации государственных служащих как неотъемлемых элементы прохождения государственной службы. На основании исследования, в первую очередь, европейского опыта правового регулирования этих элементов, автор предлагает использовать некоторые позитивные аспекты такого правового регулирования для улучшения законодательства Украины о государственной службы. Ключевые слова: государственная служба, государственная служащий, аттестация, оценивание деятельности, европейский опыт. The article describes theoretical and practical issues of evaluation and attestation of civil servants, as essential elements of the civil service. On the basis of relevant European experience of legal regulation of these elements of the civil service, the author argues the need of implementation of certain positive aspects of such legal regulation for improving the Ukrainian law on the civil service. Key words: civil service, civil servants, attestation, performance evaluation, European experience.